PENYELESAIAN SENGKETA PERJANJIAN SYARIAH PADA LEMBAGA KEUANGAN SYARIAH - Maskufa, Maskufa (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
Dispute settlement in Islamic tradition has been carried out since the era of Prophet Muhammad Saw. This is done through the  courts (litigation) and through shulh, fatwâ, mazhâlim, and hisbah, known as nonlitigation. The form of mu‘âmalah dispute settlement especially applicable nowadays is almost the same as those  prevailing at the time of the Prophet. Litigation through the judicial institutions and non litigation settlement called as alternative  dispute resolution (ADR) is known by the term shulh in fiqh, while the path through arbitration is known in fiqh as tahkîmDOI: 10.15408/aiq.v5i1.2559